Advances in drug discovery of flavivirus NS2B-NS3pro serine protease inhibitors for the treatment of Dengue, Zika, and West Nile viruses - João, Emílio Emílio [UNESP]; Lopes, Juliana Romano [UNESP]; Guedes, Bruna Fernanda Rodrigues [UNESP]; da Silva Sanches, Paulo Ricardo [UNESP]; Chin, Chung Man [UNESP]; dos Santos, Jean Leandro [UNESP]; Scarim, Cauê Benito [UNESP] (Elsevier, 2024)
Flaviviruses are vector-borne RNA viruses that seriously threaten global public health due to their high transmission index in humans, mainly in endemic areas. They spread infectious diseases that affect approximately 400 million people globally, primarily in developing countries struggling with persistent epidemic diseases. Viral infections manifest as hemorrhagic fever, encephalitis, congenital abnormalities, and fatalities. Despite nearly two decades of drug discovery campaigns, researchers have not identified promising lead compounds for clinical trials to treat or prevent flavivirus infections. Although scientists have made substantial progress through drug discovery approaches and vaccine development, resolving this complex issue might need some time. New therapeutic agents that can safely and effectively target key components of flaviviruses need to be identified. NS2B-NS3pro is an extensively studied pharmacological target among viral proteases. It plays a key role in the viral replication cycle by cleaving the polyprotein of flaviviruses and triggering the formation of structural and non-structural proteins. In this review, studies published from 2014 to 2023 were examined, and the specificity profile of compounds targeting NS2B-NS3 pro proteases for treating flavivirus infections was focused on. Additionally, the latest advancements in clinical trials were discussed. This article might provide information on the prospects of this promising pharmacological target.